Volatile biomarkers for wild mushrooms species discrimination - Malheiro, Ricardo (2014)
Secondary metabolites present in the volatile fraction of six wild mushroom species (Clitocybe odora, Clitocybe fragrans, Hebeloma crustuliniforme, Lepista nuda, Tricholoma fracticum and Tricholoma terreum) were studied, as an attempt to identify compounds capable to distinguish mushroom species for taxonomic and authentication purposes. Volatiles were assessed by headspace solid phase microextraction (HS-SPME) and by gas chromatography/ion-trap mass-spectrometry (GC/IT-MS). By using target analysis, 46 volatiles were grouped in 5 chemical classes: alcohols, aldehydes, ketones, sesquiterpene-like compounds and terpenes. Each species revealed a unique volatile profile, with changes in the dominant chemical class. Aliphatic compounds with eight carbon atoms, such as 3-octanol, 1-octanol and 3-octanone were the most abundant. The non-target approach application, using all HS-SPME-GC-MS data (raw chromatograms) aims to detect a large number of compounds to get a fingerprint of each sample. This procedure, involving previous data treatments as chromatogram data alignments, sample data fingerprints, and multivariate analysis, represents a powerful tool to execute an initial screening of the analytical results, enabling a faster interpretability of the results without time-consuming through identifications and quantifications. Unsupervised signal decomposition techniques such as principal component analysis (PCA) applied both to targeted and non-targeted approaches revealed 11 volatile compounds (3-octanol, 3-octanone, linalool, 1-octanol, 1-pentanol, (E)-2-octen-1-ol, hexanol, hexanal, (E)-2-octenal, rho-anisaldehyde and sesquiterpene-like compound) in common with an important discriminating power, suggesting that those compounds can play a crucial biomarker role in the characterization of the six wild species of mushrooms.